PENGARUH LIKUIDITAS, KECUKUPAN MODAL, EFISIENSI MANAJEMEN DAN RISIKO KREDIT TERHADAP PERTUMBUHAN KREDIT BANK UMUM DI BEI - Anjali, Ni Kadek Dewi; Sudirman, I Made Surya Negara (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.07.TAHUN.2024, 2024)
Credit distribution carried out by banks can encourage economic stability, thus banks have a role as an intermediary party. Banks distribute credit with the aim of helping parties who need funds and ensuring that the economy can run stably and to obtain profits from their business operational activities. This research aims to test and analyze the relationship between the influence of liquidity, capital adequacy, management efficiency and credit risk on commercial bank credit growth on the IDX for the period 2019 to 2022. The research data is quantitative data with secondary data sources bank financial reports published in company official website. The sample from this research was 27 banking companies selected through a randomization system using a simple random sampling technique. The analysis technique used is a multiple linear regression model. The results of the regression test analysis showed that liquidity ratios, capital adequacy, management efficiency had no significant effect on bank credit growth, while credit risk had a significant negative effect on commercial bank credit growth on the IDX. Thus, it is very important for banks to pay attention to the level of credit risk, so that banking credit growth can be better.